Doping of Sb into Cu2ZnSn(S,Se)4 absorber layer via Se&Sb2Se3 co-selenization strategy for enhancing open-circuit voltage of kesterite solar cells - Zhao, Benhui; Deng, Yueqing; Cao, Lei; Zhu, Jichun; Zhou, Zhengji (Frontiers in Chemistry, 2022)
Kesterite-structured Cu2ZnSn(S,Se)4 (CZTSSe) thin film photovoltaics have attracted considerable attention in recent years because of its low-cost and eco-friendly raw material, as well as high theoretical conversion efficiency. However, its photovoltaic performance is hindered by large open-circuit voltage (VOC) deficiency due to the presence of intrinsic defects and defect clusters in the bulk of CZTSSe absorber films. The doping of extrinsic cation to the CZTSSe matrix was adopted as an effective strategy to ameliorate defect properties of the solar cell absorbers. Herein, a novel Se&Sb2Se3 co-selenization process was employed to introduce Sb into CZTSSe crystal lattice. The results reveal that Sb-doping plays an active role in the crystallization and grain growth of CZTSSe absorber layer. More importantly, one of the most seriously detrimental SnZn deep defect is effectively passivated, resulting in significantly reduced deep-level traps and band-tail states compared to Sb free devices. As a result, the power conversion efficiency of CZTSSe solar cell is increased significantly from 9.17% to 11.75%, with a VOC especially enlarged to 505 mV from 449 mV. This insight provides a deeper understanding for engineering the harmful Sn-related deep defects for future high-efficiency CZTSSe photovoltaic devices.